Trade unions and national economic policy - Barbash, Jack.; Barbash, Kate. (Baltimore ; London : Johns Hopkins Press, 1972)
This study outlines the policies, institutions, and environments which made trade union involvement in national economic policy-or union responsibility-feasible or unfeasible in varying degrees in Sweden, Austria, the Netherlands, West Germany, the United Kingdom, and France
Includes bibliographical references and index.
lje 04/10/2018
Loans
Keywords: Labor unions; Manpower policy; Europe